Apseudomorpha (Malacostraca: Tanaidacea) of the ANDEEP III Antarctic Expedition - Jóżwiak, Piotr; Błażewicz-Paszkowycz, Magdalena (Zootaxa, 2007)
This paper presents results of studies of apseudomorph tanaidacean collected during the ANDEEP III Expedition to the Antarctic, represented exclusively by the family Apseudidae. Apseudes paragracilis Kudinova-Pasternak, 1975, A. abyssalis Błażewicz-Paszkowycz & Larsen, 2004, Leviapseudes pleonudus Błażewicz-Paszkowycz & Larsen, 2004 were previously recorded in the Antarctic abyssal. A redescription of A. paragracilis together with the description of two new species (Leviapseudes angelikae n. sp. and Collossella suprema n. gen. n. sp.) are the subject of the present paper.